The Relations between Labor Investment Inefficiency and Tax Avoidance: The Covid-19 Pandemic as a Moderating Variable - Achyar Achyar; Yulianti Yulianti (Journal of International Conference Proceedings, 2021)
This study aims to (1) analyze the relations between labor investment inefficiency and tax avoidance and (2) whether the COVID-19 pandemic moderates the relations between labor inefficiency and tax avoidance behavior in manufacturing companies in Indonesia. By using a sample of 110 manufacturing companies listed on the Indonesia Stock Exchange (www.idx.co.id) in the 2016-2020 period and processed using the Ordinary Least Squares (OLS) method, this study finds that labor investment inefficiency has a significant negative effect on tax avoidance. Moreover, Covid-19 has also strengthened the relations between labor investment inefficiency and tax avoidance.